Perlindungan Hukum terhadap Hak Cipta Karya Fotografi yang Digunakan tanpa Izin - Putu Rahayu Purnamasari; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
Photo is the result of an image taken by a camera through a photographic process carried out by a photographer and protected as one of the copyright works in the Prevailing Laws, namely the Copyright Law No. 28/2014. Violations against copyright works often occur, but there are still many photographers who do not understand or even know about copyright and the legal provisions governing and protecting it and do not register their creations with the Directorate General of IPR. So the problem that can be investigated is how the legal protection of the rights of the creator of photographic works and what legal remedies can the creator take on the work of photography that is used without permission by other people. This study aims to determine the level of legal protection for the rights of photographic creators as well as to find out the legal actions taken by the creators of photographic works that are used without the permission of others. The method used is legal research that is normative through a statutory approach as well as a conceptual approach, and the sources of legal materials used are primary and secondary legal materials with literature collection techniques which are analyzed in descriptive analytical form. Based on the results of research and analysis, it can be concluded that the copyright of photographic works is to provide protection for photo art works and to provide economic rights for the creators or copyright holders and moral rights for the creators. The route outside the court and the court route are two legal routes that can be taken in making legal remedies.